A rare case of juvenile-onset Behçet's disease: Fournier's gangrene followed by intestinal involvement. Issue 1 (January 2017) - Ayanoğlu, Burcu Tuğrul; Değertekin, Halil; Gündüz, Özge; Gürler, Aysel; Erdoğan, Fatma G.; Öziş, Salih E.
Abstract : Behçet's disease (BD) is a multisystemic, inflammatory disease with still unknown etiology and rarely seen in childhood. BD has worse prognosis in young, male patients. BD exacerbations may be triggered by viral, bacterial, and other undefined antigenic stimuli in genetically predisposed individuals. Fournier's gangrene (FG) is a rapidly progressive, necrotizing fasciitis of the genital and perineal regions with high morbidity and mortality. FG is usually seen in immunocompromised patients and may be triggered by local factors such as trauma, trombosis, and vasculitis. Here, we present a adolescent, male patient with juvenile-onset BD who developed FG and afterwards entero-Behçet. This unique assocation without any other underlying immunocompromised condition is discussed.